Caffeic Acid Phenethyl Ester Regulates PPAR’s Levels in Stem Cells-Derived Adipocytes - Luca Vanella; Daniele Tibullo; Justyna Godos; Francesca Romana Pluchinotta; Claudia Di Giacomo; Valeria Sorrenti; Rosaria Acquaviva; Alessandra Russo; Giovanni Li Volti; Ignazio Barbagallo (PPAR Research)
Hypertrophic obesity inhibits activation of peroxisome proliferators-activated receptor gamma (PPARγ), considered the key mediator of the fully differentiated and insulin sensitive adipocyte phenotype. We examined the effects of Caffeic Acid Phenethyl Ester (Cape), isolated from propolis, a honeybee hive product, on Adipose Stem Cells (ASCs) differentiation to the adipocyte lineage. Finally we tested the effects of Cape on insulin-resistant adipocytes. Quantification of Oil Red O-stained cells showed that lipid droplets decreased following Cape treatment as well as radical oxygen species formation. Additionally, exposure of ASC to high glucose levels decreased adiponectin and increased proinflammatory cytokines mRNA levels, which were reversed by Cape-mediated increase of insulin sensitivity. Cape treatment resulted in decreased triglycerides synthesis and increased beta-oxidation. Exposure of ASCs to Lipopolysaccharide (LPS) induced a reduction of PPARγ, an increase of IL-6 levels associated with a well-known stimulation of lipolysis; Cape partially attenuated the LPS-mediated effects. These observations reveal the main role of PPARγ in the adipocyte function and during ASC differentiation. As there is now substantial interest in functional food and nutraceutical products, the observed therapeutic value of Cape in insulin-resistance related diseases should be taken into consideration.